Extraction of microsomal fraction from midguts of western spruce budworm Choristoneura occidentalis F., and rat liver, and their ability to expoxidize aldrin - Mohammad, Rosli (Universiti Pertanian Malaysia, 1985)
Microsomal fractions were isolated from midguts of western spruce budworm larvae and rat liver. The microsomal preparations were then assayed for cytochrome P-450 content and aldrin epoxidase activity. Both microsomal preparations showed distinct spectrum of cytochrome P-450. Relative to protein content, the cytochrome P-450 content of midguts of western spruce budworm was lower by 7 - 9 times compared to that of the rat liver. Epoxidase activity is present in the two microsomal preparations as indicated by their ability to convert aldrin to dieldrin. The activity of both microsomal preparations was inhibited by piperonyl butoxide.